Urgency of Spatial Planning of the Mataram City Library and Archives Office in Increasing Interest In Visiting Libraries in Mataram City - Iwin Ardyawin (Literatify: Trends in Library Developments, 2023)
The primary issue in this study is how the Mataram city library's spatialplanning affects the number of visitors who are interested in MataramCity’s library. In order to increase the interest of visiting users in the cityof Mataram, it will be discussed how the roles and limitations of theMataram city library's physical layout affect its services. The researchmethod used in this study was descriptive qualitative research, and theprimary data source was interviews and field observations. Secondarydata sources included documentation, journals, websites, scripts, andother sources, as well as results from other types of research. Thestudy's findings show how the Mataram city library service can increasethe interest of readers who are visiting the city by using a variety ofelements, including space (layout), library rooms, facilities, ventilation,and color, while the library service's challenges must be overcome.There aren't many rooms because The Library Service of Mataram Cityis still in the planning or development stage.